A Study Of Covid Impact On Teaching Pedagogy And Academic Institutions - Mrs. Jalpa H. Panery; Dr. Meghashree Dadhich (Educational Administration: Theory and Practice, 2024)
Toutbreak of Covid 19 pandemic has critically disrupted each and every aspects of human life including education. It has created unpredictable situation in the area of education around the world. In India government announced lockdown on 22nd March, 2020. Due to that campuses of education institutions mainly school, colleges and universities were closed and teaching and learning has transformed in online mode. In India, approximately 32 crore learners teaching, learning and research stopped. It was the biggest challenge in front of entire education sector. It has been said that necessity is the mother of Inventions. New and innovative ways of teaching and learning tools, techniques, software and new prospects emerged during pandemic time. After Pandemic, introduction of New Education Policy 2020 emphasis on quality, affordability, accountability, universal accessibility of education, multidisciplinary education, institutional sovereignty, promote research which leads to faster transformation of knowledge in to Society.[22] Every coin has two sides, proves true in case of teaching and learning through digital platform. The objective of this paper is to analyze impact of covid on teaching and academic institutions in India, challenges faced by teachers, students and academic institutions, sources of online learning, post covid consequences, new teaching pedagogies after covid. The study will provide the opportunity to pave the way for ministry and related authorities to develop and boost awareness regarding digital learning for beneficiaries academic institutions in India.